2021
DOI: 10.3389/fpsyg.2021.587943
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Crime and Other Uses of Neural Networks in Police Decision Making

Abstract: Neural networks are a machine learning method that excel in solving classification and forecasting problems. They have also been shown to be a useful tool for working with big data oriented environments such as law enforcement. This article reviews and examines existing research on the utilization of neural networks for forecasting crime and other police decision making problem solving. Neural network models to predict specific types of crime using location and time information and to predict a crime’s locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Recent studies have demonstrated the predictive power of Artificial Neural Networks (ANN) associated with its ability to approximate any continuous function. ANN are utilized in a wide of variety of applications in engineering, technology and time series forecasting in fields such as biology, finance, medicine and economics social science (Dilek et al, 2015 ; Fu et al, 2018 ; Palmer et al, 2008 ; Walczak, 2021 ). ANN are robust in their application, which include tasks related with pattern classification, the estimate of continuous variables and time series forecasting (Kaastra & Boyd, 1996).…”
Section: Analysesmentioning
confidence: 99%
“…Recent studies have demonstrated the predictive power of Artificial Neural Networks (ANN) associated with its ability to approximate any continuous function. ANN are utilized in a wide of variety of applications in engineering, technology and time series forecasting in fields such as biology, finance, medicine and economics social science (Dilek et al, 2015 ; Fu et al, 2018 ; Palmer et al, 2008 ; Walczak, 2021 ). ANN are robust in their application, which include tasks related with pattern classification, the estimate of continuous variables and time series forecasting (Kaastra & Boyd, 1996).…”
Section: Analysesmentioning
confidence: 99%
“…Given these benefits, ML procedures have been gaining visibility and strength in Applied Social and Health Sciences. Some works have focused on predicting different types of crimes, and even the location of where they occur, using neural networks and Multilayer Perceptron (MLP) [21]. But there has also been a proliferation of works that aim to predict the type of IPV with Random Forest and SVM classifiers [22] or use neural networks to determine accurate predictors of this type of violence [23].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, crime rate has been on the increase within public universities. As the population of a country increases, crime rates within that country increases (Walczak 2021). This also impacts the accurate prediction of crime (Pratibha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%